Design Improvement On Trimming Workstation For Aerospace Company Based On Ergonomics Analysis (Case Study at CTRM AC Sdn Bhd) - Halimah , Abd Halim (UTeM, 2010)
The application of ergonomic principle is highly essential in the development of workplace to protect workers health and safety. The development and awareness on safety and comfortability brings worker quality performance. This study was performed at CTRM AC Sdn. Bhd. CTRM AC is located at Malacca which is one of the aircraft manufacturer based on the composite part. This study is focusing on the trimming process, which one of main activities that invovled in manufacturing A320 Movable Fairing panel. Trimming process required a jig to trim onto shape in order to meet customer requirement quality. Trimming of composites material has becomes one of the most hazardous processes that affect human health. From the ergonomic side, the lack of adapting the ergonomic principles would impair performance of workers. In this research, ergonomic principle is introduce as fundamentals in redesigning trimming workstation.The workstation is redesign based on anthropometry data. The data collect through the questionnaire, observation and an informal interview with the workers. Futhermore, RULA Analysis performed by using CATIA V5 software. As a result, the new propose design of trimming workstation was developed.